(3faMI GdQjMGfI hQTMI WdGA GdMGfIs - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeQ GdNaGLj GdeUQj,J (B1069 (3g` s
(3ChdgG (B:s
(3CfRdg Gddg hCSHMg hCSCdg GdJhajb hGSJefMg s
(3BNQgG (B:s
(3dFf VGbJ Hi GdCjGe PQYkG aUHQi ePgH eG YTJ cQHi NdUJ ef GdCeGfi ai MjGJi aCQLh ai eeGJi Yah QHi s
(3GdbSe GdChds
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B227s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B170 s
Keywords: (3GdJGQjNs